Manganese-Coordinated Lipid Nanoparticles for Co-Delivery of VZV Antigen and CpG Adjuvant Enhance Vaccine Efficacy - Liping Luo; Xinyue Deng; Jia Luo; Zhengmiao Zhou; Ye Liu (Zoonoses, 2025)
<!-- named anchor --> Objective: Because varicella zoster virus (VZV) infections are continually increasing, vaccine efficacy must be enhanced. To date, the inefficient in vivo utilization of antigens and adjuvants has limited vaccine-induced immune protection against VZV infection. Therefore, improving the antigen and adjuvant utilization efficiency is crucial to enhance VZV vaccine performance. <!-- named anchor --> Methods: To achieve favorable VZV antigen and adjuvant utilization efficiency, we constructed a co-delivery system based on manganese-coordinated lipid nanoparticles (Mn-LNPs). Palmitic acid was coordinated with manganese through hydrothermal synthesis. Furthermore, 1.6 molar palmitic acid-Mn was added to four commercial lipid nanoparticle components (SM-102:DSPC:CHO-HP:DSG-PEG2000 in a 50:10:37.5:2.5 molar ratio) to encapsulate VZV glycoprotein E (gE) antigen and CpG adjuvant by using a microfluidic chip. We characterized Mn-LNP size and morphology through transmission electron microscopy and quantified the manganese on palmitic acid-Mn through X-ray photoelectron spectroscopy. We also evaluated the performance of the Mn-LNP co-delivery system in enhancing VZV vaccine-induced immune responses in a mouse model. <!-- named anchor --> Results: The Mn-LNPs comprised positively charged spherical particles of approximately 270 nm in diameter, which encapsulated VZV gE antigen and CpG adjuvant in a 1:2 mass ratio. The Mn-LNP co-delivery system, compared with aluminum adjuvant, significantly enhanced VZV gE antigen-specific CD4 + and CD8 + T cell responses (1.47-fold and 5.66-fold enhanced IFN-γ response for CD4 + T cells and CD8 + T cells; 2.25-fold and 2.64-fold enhanced TNF-α response for CD4 + T cells and CD8 + T cells; and 2.62-fold and 3.17-fold enhanced IL-2 response for CD4 + T cells and CD8 + T cells). Moreover, the Mn-LNPs, compared with commercial aluminum adjuvant, significantly enhanced the antigen-specific IgG2b subclass response. <!-- named anchor --> Conclusion: The Mn-LNP co-delivery system efficiently delivered both VZV antigen and CpG adjuvant, and markedly improved the VZV vaccine-induced T cell response. Thus, this Mn-LNP co-delivery system has promising potential in promoting VZV vaccine efficacy.